Effects of machining parameters on surface quality of composites reinforced with natural fibers. Issue 1 (2nd January 2021) - John, Raveen; Lin, Richard; Jayaraman, Krishnan; Bhattacharyya, Debes
ABSTRACT: To minimize the surface roughness and delamination problems during the end milling of natural fiber reinforced composites (NFRCs), it is essential to understand the effects of the machining parameters (spindle speed and feed rate) and the kinematics of material removal. In this study, the effects of machining parameters on the machined surface quality – surface roughness (Ra ) and delamination factor (Fd ), during end milling of kenaf, jute and rice husk (RH) reinforced polypropylene (PP) composites has been analyzed using a two-factor, three-level experimental plan. It has been noticed that there are significant differences in the silicon contents (kenaf: 0.57%, jute: 4.16% and RH: 22.2%) and hardness values (kenaf: 0.15, jute: 0.20 and RH:0.59 GPa) of the three natural fibers, which has influenced the resulted surface quality of the machined NFRCs. Kenaf/PP composites showed the lowest delamination damages and the best surface finish most likely due to the fiber composition and morphology of kenaf, while predictably, RH/PP composites were the most demanding to machine. With a statistical analysis on the results, it is concluded that the machined surface quality is more influenced by spindle speed with percentage contribution showing at least three times more than feed rate for machining NFRCs.